Distraction Techniques: Story Telling With Anxiety Problems In Children With Diarrhea - Rosyadah, Ambrina; Jawiah; Rehana (Yayasan Rumah Ilmu Professor, 2023)
Hospitalization causes anxiety in children and hinders the healing process, distraction techniques: story telling is a nursing action that is able to distract anxiety and is able to create a comfortable environment so that the level of anxiety experienced by children can decrease. Method: This type of research design uses a descriptive design in the form of a case study. The approach used is nursing care which includes assessment, nursing diagnosis, planning, implementation, evaluation and documentation. The case study subjects used were 2 pediatric patients suffering from diarrhea aged 4 years for patient 1 on March 18 2022 and aged 6 years for patient 2 on March 23 2022 who had the same nursing problem, namely anxiety. This research was conducted at Siti Fatimah Regional Hospital, Palembang in 2022. Results: The implementation of nursing in the form of distraction techniques: story telling has an effective effect on reducing the anxiety experienced by pediatric patients during treatment. The results show that the patient's anxiety score has decreased significantly and determine the patient's anxiety level before and after administering the distraction technique. Conclusion: Providing the distraction technique: story telling with anxiety problems was effective in reducing anxiety, there was a significant reduction after using the distraction technique: story telling for three days.